Fundação Casa Grande - Memorial do Homem Kariri: cotidiano, saberes, fazeres e as interfaces com a educação patrimonial - Noronha, Isabelle de Luna Alencar (2008)
The following research paper discusses the educational practices of Casa Grande Foundation Homem Kariri Memorial, a NGO that works with education, communication, art and culture in the countryside of Ceará State. It consists of a bibliographical and ethnographical study, whose theoretical-methodological referential is the Oral History. During this work, it was searched to understand how a NGO, like Casa Grande Foundation, which is known for the fact that is managed by children, teenagers and young, who are protagonists of their teaching and learning processes, got the success as a consistent educational project, attracting the eyes of the world for it, over its fifteen years of existence. For this, an incursion was necessary in the complex world of NGOs and in the national and state policies of incentive to culture. We locate the interfaces of non-formal education in Casa Grande Foundation, with the patrimonial education, because it works with the local culture through researches, valorization and caring of Cariri Region Archeology, in Ceará. The patrimonial education in the everyday Casa Grande Foundation s knowledge and creations propitiate the development in boys and girls the feeling of making part a place, which can be reflected in practices of conscious and active citizenship for the preservation of immaterial and material patrimony in Cariri Region, Ceará, throughout their lives.